Evaluation of Some Phenotypic, Physiological and Egg Quality Traits of African Black Neck Ostrich under Arid Desert Conditions of Libya - El-Safty, S.; Mahrose, Kh. M. (International Journal of Poultry Science, 2009)
Twenty birds of African Black Neck Ostrich (10 of both males and females) were used in the present study in a completely randomized design to verify and evaluate the differences between males and females of ostrich in some phenotypic and physiological traits, likewise the egg quality traits were estimated under the poor desert conditions of south Libya. The main results of the present study showed that males of ostrich were taller (p